An In-Depth Look at How to Run Strategies Using Social Media and New Ideas from Companies - Hari, Minti (Malacca: Journal of Management and Business Development, 2025)
This research aims to gain a deeper understanding of the use of social media and business innovation in company growth strategies. Researchers applied qualitative research methodology, using semi-structured interview techniques to examine follow-up questions that could answer the study's objectives. Interviews were conducted with several MSMEs in Thailand, who served as the research subjects, totaling 20 respondents. The research results indicate that social media usage can help build better consumer-customer relationships, leading to increased loyalty. Effective business innovation can also create a favorable impression and provide significant information and recommendations to influence purchase decisions. Businesses that effectively utilize social media will have stronger connections compared to those that do not engage with corporate social media platforms.